Counseling against Traffic Violations by Drivers Under The Influence of Alcohol (Case Study in Surakarta City) - Raga Farros Al Bassith; Marisa Kurnianingsih (Universitas Muhammadiyah Surakarta, 2023)
The aim of conducting the research is to find out: (1) traffic violations by drivers under the influence of alcohol in the City of Surakarta based on Law Number 22 of 2009; and (2) efforts to overcome traffic violations by drivers under the influence of alcohol in the city of Surakarta. In Indonesia, especially in big cities, the traffic situation is still far from orderly, the cause of traffic violations is someone who deliberately drives under the influence of alcohol. With the help of empirical juridical research methods,through field research which focuses on collecting empirical data in the field so that it canreviewing the implementation of criminal law policies regarding traffic violations committed by drivers under the influence of alcohol at the Surakarta Police through interviews and the implementation of Law Number 22 of 2009 concerning Road Traffic and Transportation. The results of these findings state that as a form of law enforcement against traffic violations by drivers under the influence of alcohol in the city of Surakarta, it is basically in accordance with the applicable regulations of Article 311 of the LLAJ law. Efforts to overcome the occurrence of traffic accidents in the city of Surakarta with the aim of providing comfort for road users through education, advocacy, outreach and campaigns.